Gurguéia nut: a new and potential fruit crop - Cavalcante, Ítalo Herbert Lucena; Osajima, Josy Antevelli; Falcão Neto, Raimundo; Silva, Roberto Lustosa (Comunicata Scientiae, 2015)
Still practically unknown in the world fruit market, Gurguéia nut (Dipteryx lacunifera Ducke) is leguminous fruit species native to Brazilian Mid-North region) whose almond is very appreciated by native people. Nevertheless, these species are not very well known. The aims of our work were first to evaluate thoroughly the literature currently available on Gurguéia nut and secondly to supplement this review by agronomic works published about it. Origin and distribution. The study includes a presentation of the origin, geographical distribution and phenotypic variability of Gurguéia nut. Botanical classification and taxonomy. The study includes a presentation of the botany, morphology and floral biology of Gurguéia nut. Plant propagation. The methods available for plant propagation of Gurguéia nut are focused and properly described, with examples of published manuscripts. Compositions and uses. The many uses of Gugrguéia nut plant parts are presented with especial consideration for its almond composition in relation to nutrients, vitamins, proteins and fatty acids, as well as the various possibilities of processing. Conclusion. Our review highlights the fact that the interest shown in Gurguéia nut is recent and, for these reasons, more detailed knowledge on these species is required (agronomic, genetic and technological).